Characterization of chemo-sensitization and apoptosis signaling mechanisms mediated by Ad-MBRG recombinant adenovirus in human cancer cell lines - Tan, Ee Wern * (2023)
Cancer is one of the major leading causes of mortality globally and chemo-drug-resistant cancers pose significant challenges to cancer treatment by reducing patient survival rates and increasing treatment costs. Although the mechanisms of chemoresistance vary among different types of cancer, the cancer tumour cells share several hallmarks of cancer, including resistance to apoptosis such as apoptosis mediated by the mitochondrial signalling pathway as well as the ability of the tumour stem cells, which is present in a small population within the tumour, to undergo cellular differentiation by producing metastatic daughter cells that are resistant to chemotherapy. To overcome the resistance to apoptosis, a tetracistronic gene therapy expression construct, consisting of adenovirus mediated expression of Ad-MBR-GFP (MOAP-1, BAX, RASSSF1a, and GFP), targeting mitochondrial apoptosis pathway was generated to promote apoptosis signalling in chemo-drug resistant human breast cancer cells, MCF-7-CR and MDA MB 231. This can be evidenced by the presence of nuclei condensation and annexin-V positive cells in the cancer cell population infected by Ad-MBR-GFP. Furthermore, our results showed that the chemo-resistance of MCF-7-CR and MDA MB 231 cells coincided with the expression of cancer stem cell marker, CD44 as these cells were identified as CD 44+/CD 24- cells with an elevated level of endogenous ALDH activity, that is in sharp contrast to chemo-drug sensitive SNU-1581 breast cancer cells which were identified as CD 44-/CD 24- cells with a low level of endogenous ALDH activity However, the chemo-resistance of both MCF-7-CR and MDA MB 231 cells was negatively impacted by the treatment with Ad-MBR-GFP and cisplatin, leading to 9-Fold reduction in the IC50 values 183 μM to just 20 μM at 24 hours when compared to cisplatin treatment alone in MCF7-CR. The data were further supported by 3D (soft agar) and spheroid cell models which showed that Ad-MBR-GFP plus cisplatin treatment reduced the number of cell colonies and spheroids of both MCF-7-CR and MDA-MB-231 cells by approximately 2-fold to 35% and 43%, respectively when compared to cisplatin treatment alone. Other than chemosensitivity, MBR-GFP significantly retarded the cell migration of both MCF-7-CR and MDA-MB-231 cells as well as SH-SY5Y cells, a CD24-positive cell line with a high level of endogenous ALDH activity. Flow cytometry analysis showed that the mechanism of action of MBR-GFP involves inducing cell cycle arrest at the G1 phase and reduction at the S phase in MCF-CR-7 cells, suggesting that chemo-sensitization mediated by AdMBR-GFP activates both apoptosis and cell cycle arrest of cancer cells, concluding that, Ad-MBR-GFP as a potentially efficacious treatment for chemo-drug resistant cancers.